The Impact of Social Media on Customer Satisfaction Using Kano’s Model - Kamali, Mohammad (Digital Repository of Theses, 2026)
One of the most critical determinants of success in any industry is customer satisfaction. Consequently, organizations focus adamantly on customer perception to improve customer satisfaction with their products. Although the Kano model has been widely applied to elicit customer service quality requirements and enhance customer satisfaction, its implementation in the social media field remains in its infancy, and ambiguity exists regarding customer needs related to technology domains. The purpose of this study is to gain a deeper understanding of how Kano's model can influence customer satisfaction in a digital context, which may lead to improved customer loyalty and brand differentiation in a competitive business environment. The study employs a mixed-methods (quantitative and qualitative) approach by applying a cross-sectional research design. This research is conducted through a random sampling of 400 social media users from around the world, using online surveys from April to June 2025, yielding significant results. Three data instruments are applied to collect relevant data: a) surveying by applying an online questionnaire (quantitative) that covers perceptions of different features of social media and their effects on customer satisfaction, b) interviews with specialists in the social media industry (qualitative), and c) content analysis of secondary data (qualitative). The findings indicated that features like “prompt responsiveness" and “consistent posting,” known as Must-Be features, and “genuine, personal responses” and “exclusive loyalty benefits” emerged as One-Dimensional features. Additionally, features like “customized content”, “consistent brand visuals”, “active hashtag monitoring”, and “account security”, known as Attractive features, resulted from carefully examining consumer behavior using the statistical model (SEM model) and Kano's model. Additionally, the findings indicate that organizations should invest in unique and specialized strategies and project control tips, as outlined in the model results presented in this dissertation, to enhance customer satisfaction. Moreover, the recommendation for future research is to focus on a specific company. Based on the survey findings from participants worldwide, future studies should examine cultural differences in customer perception to understand better how customer expectations vary across different geographical regions and demographics. Keywords: Social media, Consumer satisfaction, Kano Model, SEM Model, Strategy